Future of currency: a comparison between traditional, digital fiat and cryptocurrency exchange mediums. (7th August 2020) - Khan, Mohammad Zainullah; Ali, Yousaf; Sultan, Hassan Bin; Hasan, Muhammad; Baloch, Salar
The ever-increasing computing power backed by Moore's law and the rapid breakthroughs in encryption has transformed the way currency is transferred and used. While the traditional government-controlled currency maintains its dominant position, a new virtual currency known as cryptocurrency has sprung up. It competes head-on by decentralizing the system, facilitating peer-to-peer transactions, and offering a universal exchange medium. However, the phase shift process is in its early stage, hindered by doubts in the mind of the public. In this paper, a comparison has been made between traditional, digital fiat and cryptocurrency, using the technique for order of preference by similarity to ideal solution (TOPSIS). It helped to ascertain the current level of awareness amongst the people of Pakistan and their likelihood of adopting the virtual currency. A forecasting approach along with a case study is also employed to see the future trends and security concerns revolving around the new medium.